Regulation of the Dopamine and Vesicular Monoamine Transporters: Pharmacological Targets and Implications for Disease - German, Christopher L.; Baladi, Michelle G.; McFadden, Lisa M.; Hanson, Glen R.; Fleckenstein, Annette E. (Pharmacological reviews, 2015)
Dopamine (DA) plays a well recognized role in a variety of physiologic functions such as movement, cognition, mood, and reward. Consequently, many human disorders are due, in part, to dysfunctional dopaminergic systems, including Parkinson’s disease, attention deficit hyperactivity disorder, and substance abuse. Drugs that modify the DA system are clinically effective in treating symptoms of these diseases or are involved in their manifestation, implicating DA in their etiology. DA signaling and distribution are primarily modulated by the DA transporter (DAT) and by vesicular monoamine transporter (VMAT)-2, which transport DA into presynaptic terminals and synaptic vesicles, respectively. These transporters are regulated by complex processes such as phosphorylation, protein–protein interactions, and changes in intracellular localization. This review provides an overview of 1) the current understanding of DAT and VMAT2 neurobiology, including discussion of studies ranging from those conducted in vitro to those involving human subjects; 2) the role of these transporters in disease and how these transporters are affected by disease; and 3) and how selected drugs alter the function and expression of these transporters. Understanding the regulatory processes and the pathologic consequences of DAT and VMAT2 dysfunction underlies the evolution of therapeutic development for the treatment of DA-related disorders.